STRATEGI PENGEMBANGAN USAHA DELICIA DALAM MENINGKATKAN PENDAPATAN - Delaksmi Armareta,; Reza Widhar Pahlevi, (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
Delicia is a business operating in the culinary sector. Culinary businesses seem to be inseparable from people's lives, considering that consuming food provided by culinary businesses is part of their daily needs. This business development is to find out the focus of Delicia products that will be developed so that they can compete with existing market snack businesses so that it is a business worth developing. Delicia sells various kinds of cakes, for example mochi, risol mayo, cheese roll, pudding, etc. which are currently still being sold in the SMP N 2 Tempel canteen. Even though there are instant and modern foods imported from abroad, market snacks are still popular for several reasons, including relatively affordable prices with good taste, and many varied choices provided. This research aims to improve Delicia's business development strategy. This strategy uses the BMC (Business Model Canvas) approach and uses SWOT analysis (Strengths, Weakness, Opportunity, Threat). Where BMC is considered effective in business development. Meanwhile, SWOT is to find out strengths, weaknesses, threats and opportunities in business